Crecimiento de Schinopsis quebracho-colorado (Schlecht.) Barkl. et Meyer, Anacardiaceae - Giménez, Ana María; Ríos, Norfol A. (Instituto de Ecología, A.C., 2016)
The Argentinian Chaco is the most extensive phytogeographic region of the country. The forest resource is the principal source of wealth, and it is found in an alarming state of deterioration. The objective of this paper is to explain the growth as a function of age of Schinopsis quebracho-colorado (Schlecht.) Barkl. et Meyer, Anacardiaceae. Ten trees with DBH (diameter at breast height, 1.3 m) over 30 cm, from the natural forest of Los Pirpintos, Copo Department, Santiago del Estero, Argentina, were studied. The methodology adopted for the study is that of Helinska. Growth was determined by epidometric analysis.Growth rings are moderately boundary distinct (type 3 Coster). Average tree ring thickness is 2.19 mm (1.6 y 4.5). Ring thickness varies significatively with age and is not correlated with this variable. Growth rings have a maximum thickness at 61 years old.The evolution of shaft volume and the age are positive correlated, the same as the diameter, normal section and total height. The variables DBH, normal section area, total height, MIA, IA and age adjusted to second degree polynomial functions. Crown diameter/age, crown diameter/DBH, crown section/normal section area adjusted to logarithmic functions. DBH correlates positively with crown diameter and age. For the relationships of growth it is estimated a technological cut shift over 250 years.